Hepatitis update program: need of the situation to co-manage viral hepatitis and COVID-19 - Keshan, Pranav; Rastogi, Aayushi; Syed, Sabin; Ramalingam, Archana; Sharma, Tarika; Kumar, Vinay; Bansal, Akanksha (International Journal of Research in Medical Sciences, 2021)
Background: Government of India has taken several initiatives towards combating viral hepatitis but due to sudden surge in COVID-19 cases resulted in suspension of viral hepatitis program related activities. Moreover, COVID-19 has several liver related complications hence more special precautions are required to manage patients with known liver diseases. Nurses play an important role in management of any disease. However, there is limited knowledge among nurses on co-management of COVID-19 and viral hepatitis. With this background, two-day training program for nursing professionals was conceptualized under the project PRAKASH to educate and train the nurses about co-management of COVID-19 and viral hepatitis. Methods: A pre-post study was undertaken among nurses who have registered for hepatitis update program. The online link to 25-knowledge related questions along with demographic variables was shared with the registered participants. Paired t test and other statistical analyses were done using SPSS v-21. Level of significance was taken at p<0.05 Results: A total of 1151 responses were received out of 1477 trained participants. The mean age of the nursing participants was 32.5±6.95 years. The overall mean knowledge score in the pre-assessment was found to be 15.47±4.13 out of 25, which further increased to 20.72±3.81 in the post-assessment. Gender, type of facility, education, willingness to get trained and prior training related to viral hepatitis were found to be independently associated with pre-knowledge score. Conclusions: Training programs should be encouraged for diseases which are of public health importance and can’t be ignored with respect to increasing burden of COVID-19 cases.